PTH-134 'hands-on' ERCP courses: can quality and safety be maintained?. (8th June 2018) - Frost, John; Alame, Riad; Deakin, Mark; Durkin, Damien; Glass, Robert; Lau, Kar; Wardle, Terence; Green, Jonathan; Hebbar, Srisha
Abstract : Introduction: Nationally there is a drive amongst endoscopists to improve both procedural quality and safety through standardisation and sharing of best practice amongst trainers and trainees. This is perhaps most evident in colonoscopy where a number of KPIs and procedural evaluation tools (DOPyS) have been established in order to meet the requirements for JAG accreditation. ERCP however seems to have lagged behind with no existing formal evaluation process in the UK, yet is arguably a more challenging procedure with more inherent risks than standard endoscopy. It is imperative that high quality ERCP training be delivered safely, and therefore we have reviewed our 'hands-on' ERCP course data over the last 10 years to see if we're achieving this. Methods: RSUH provides 'Hands-on' ERCP courses in both basic and advanced skills training, and 'train the trainer' (TTT). Course data from 2007 – 2017 was collected from the 'Unisoft' endoscopy reporting system, the 'iSoft Clinical Manager' (iCM) and 'Medisec' databases. They were evaluated for the following: Procedural success using standards outlined in the BSG's 2014 'ERCP service framework': ≥85% cannulation rate of virgin papillae, CBD stone clearance for ≥75% of those undergoing their 1 st ERCP, Successful stenting at 1 st ERCP where required in ≥80%. Patient safety; comparing our risk of procedural related adverse events against those quoted in the literature. Delegate feedback was also reviewed where possible. Results: Biliary cannulation was successful in 304/345 (88%) of patients with a virgin ampulla, and in 443/495 (89%) patients overall. Complete stone clearance was achieved in 75% of patients at index endoscopy, and stents were successfully deployed in 98% of biliary strictures. Complications occurred in 32 (6%) patients: 18 (4%) cases of bleeding, 9 (2%) cases of pancreatitis, 2 (0.4%) cases of perforation, Feedback was positive, with delegates finding the courses organised, helpful, and informative. Conclusions: Royal Stoke University Hospital (RSUH) has been at the forefront of delivering 'hands-on' ERCP courses year on year. Our 10 year data is reassuring for both trainers and trainees and suggests that such courses are both safe and capable of providing high quality ERCP for patients in attendance.